PENGARUH AKTIVITAS PERDAGANGAN TERHADAP RETURN SAHAM SYARIAH PERUSAHAAN YANG LISTING DI JAKARTA ISLAMIC INDEX (JII) PERIODE 2012 – 2014 - Rini Elvira (Jurnal Madania)
The Effect of Trading Activity on the Sharia Return Share Company Listed in Jakarta Islamic Index (JII) During 2012-2014. This article is aimed at investigating whether trade activities such as frequency, volume, trading day where simultaneously and partially affected to sharia companies stock return listed on JII period 2012-2014. The samples of this study were 17 companies during three periods. The results of the research showed that (1) trading frequency, trading volume, and trading day were simultaneously affected to the syariah companies return stock at alpha 1%, (2) trading frequency was affected positively but it was not significant to the syariah companies, (3) trading volume was affected significantly positive to the syariah companies at alpha 1%, (4) trading day was affected positively but it was not significant to the syariah companies stock return, (5) the capability of trading frequency, trading volume, and trading day simultaneously affected syariah companies listed on JII period 2012-2014 was 17, 8%, and (6) the capability of trading volume partially affected syariah companies stock return listed on JII period 2012-201 was 22, 6%.